GEMMA: An Earth crustal model based on GOCE satellite data - M. Reguzzoni; D. Sampietro (International Journal of Applied Earth Observation and Geoinformation, 2015)
The boundary between Earth's crust and mantle is commonly modelled as a discontinuity surface, the so-called Moho. Although in some regions of the world this model may be too approximate or even unrealistic, globally speaking it can provide a key to read several long wavelength geophysical signals. Recent research activities have shown the possibility to estimate the Moho discontinuity worldwide from global gravity field model, however usually the solution of this inverse problem requires strong unrealistic hypotheses. In this work a new procedure to relax some of these unrealistic hypotheses is devised and described in details. Basically it allows to estimate the mean Moho depth even once the normal gravitational field is removed if at least one seismic observation is available, to take into account the dependency of the crust density on the radial direction (usually neglected in Moho depth determination from gravity), to correct the a-priori density model of the crystalline crust for scale factors again using seismic information and finally to consider a Moho with a non-constant depth as reference surface in the inversion, thus reducing the linearization error. The new procedure is here applied to GOCE data to estimate a new crustal model. For this purpose additional external information has been used, such as topography, bathymetry and ice sheet models from ETOPO1, a recent 1° × 1° sediment global model and some prior hypotheses on crustal density. In particular the main geological provinces, each of them characterized by its own relation between density and depth, have been considered. A model describing lateral density variations of the upper mantle is also taken into account. The new crustal model is computed at a spatial resolution of 0.5° × 0.5°, its gravitational effect differs from GOCE observations of 49 mE and its Moho depth error standard deviation is globally of 3.4 km. Therefore the result seems to be an improvement in terms of resolution, consistency with the gravity field and accuracy not only ...